Persepsi Masyarakat Mengenai Efektivitas Iklan Retail Modern Indomaret di Kecamatan Biringkanaya - Khaedir Baharuddin (Journal of Communication Sciences (JCoS), 2020)
This study aims to determine the effectiveness of Indomaret modern retail advertisements in Biringkanaya District. The method used is qualitative, by interviewing informants in accordance with the research objectives. From the results of the study, it was concluded that Indomaret Store consumers have given a positive perception of promotional advertisements in brochure print media and Indomaret online media or social media. In terms of intensity or frequency, consumers' perceptions are very good because they are published regularly once a week. However, consumers also state that there are still many shortcomings of print media brochures such as pictures and text prices that are blurred / blurry and less varied in terms of color and writing. Consumer perceptions of online media and social media are also positive. This is because in terms of intensity, Indomaret promo ads can be accessed at any time, in terms of clarity it is also good because it presents clear, varaitive images, colors and writing. In terms of attractiveness, most consumers recognize that online media and social media product advertisements are more attractive than print media because they use a combination of faster intensity and clarity of images, text and color. Furthermore, the factors that influence consumer perceptions of Indomaret advertisements are Internal / functional factors which include needs factors and mental readiness and mood factors. While external factors are the existence of stimuli / repetitive stimuli, message content that fits the needs and attitudes of employee behavior and good experience from consumers.